The Effect of Operating Cash Flows and Book Tax Differences on Profit Growth in Large Trading and Small Trading Sub-Sector Companies Listed on the Indonesia Stock Exchange - Cindy Ramli (Outline Journal of Economic Studies, 2022)
This study aims to determine the effect of operating cash flow and book tax difference on profit growth in large and small trading sub-sector companies listed on the Indonesia Stock Exchange. The research methodology used is a quantitative descriptive method. The population in this study are large and small trading sub-sector companies totaling 61 companies. The results of the research analysis show that operating cash flow has no significant effect on profit growth in large trading and small trading sub-sector companies based on the results of partial hypothesis testing. The results of the research analysis show that Book Tax Difference has a significant effect on Profit Growth in Large Trading and Small Trade Sub-Sector Companies based on the results of partial hypothesis testing. The results of the research analysis show that Operating Cash Flow and Book Tax Difference have a significant effect on Profit Growth in Large Trading and Small Trading Subsector Companies based on the results of simultaneous hypothesis testing.